Truncating Prolactin Receptor Mutations Promote Tumor Growth in Murine Estrogen Receptor-Alpha Mammary Carcinomas - Obi L. Griffith; Szeman Ruby Chan; Malachi Griffith; Kilannin Krysiak; Zachary L. Skidmore; Jasreet Hundal; Julie A. Allen; Cora D. Arthur; Daniele Runci; Mattia Bugatti; Alexander P. Miceli; Heather Schmidt; et al. (Cell Reports, 2016)
Estrogen receptor alpha-positive (ERα+) luminal tumors are the most frequent subtype of breast cancer. Stat1−/− mice develop mammary tumors that closely recapitulate the biological characteristics of this cancer subtype. To identify transforming events that contribute to tumorigenesis, we performed whole genome sequencing of Stat1−/− primary mammary tumors and matched normal tissues. This investigation identified somatic truncating mutations affecting the prolactin receptor (PRLR) in all tumor and no normal samples. Targeted sequencing confirmed the presence of these mutations in precancerous lesions, indicating that this is an early event in tumorigenesis. Functional evaluation of these heterozygous mutations in Stat1−/− mouse embryonic fibroblasts showed that co-expression of truncated and wild-type PRLR led to aberrant STAT3 and STAT5 activation downstream of the receptor, cellular transformation in vitro, and tumor formation in vivo. In conclusion, truncating mutations of PRLR promote tumor growth in a model of human ERα+ breast cancer and warrant further investigation.